Clinical epidemiology, risk factors and treatment outcomes of extended-spectrum beta-lactamase producing Enterobacteriaceae bacteremia among children in a Tertiary Care Hospital, Bangkok, Thailand - Thirapa Nivesvivat; Phunlerd Piyaraj; Sudaluck Thunyaharn; Veerachai Watanaveeradej; Detchvijitr Suwanpakdee (BMC Research Notes, 2018)
Abstract Objective Extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae infection is an emerging problem in paediatric populations leading to increased mortality. The purpose of this study was to determine the prevalence, risk factors and clinical outcomes of ESBL-producing Enterobacteriaceae in paediatric blood stream infections (BSIs). A retrospective review of paediatric patients diagnosed with Enterobacteriaceae bacteremia was performed at Phramongkutklao Hospital from 2010 to 2017. Results Among 97 non-duplicated blood isolates, the prevalence of ESBL-producing Enterobacteriaceae was 53.6% (28.9% Escherichia coli and 25.8% Klebsiella spp. isolates). The study indicated that the prevalence of ESBL infection was higher among patients with chronic illness, especially hematologic malignancies, than among patients without underlying disease (P = 0.01). No differences were observed in the prior use of any antibiotics, the use of extended-spectrum cephalosporin, neutropaenia or the presence of an indwelling central venous catheter. Mortality in the ESBL group was significantly higher than that in the non-ESBL group, with observed mortalities of 38.9% and 13.3%, respectively (P < 0.05). In conclusion, BSIs with ESBL-producing Enterobacteriaceae tended to increase infection rates and impact survival rates among paediatric patients.